Are You My Candidate? Gender, Undervoting, and Vote Choice in Same-Party Matchups. Issue 3 (September 2022) - Stauffer, Katelyn E.; Fisk, Colin A.
Abstract: Partisanship is the dominant force that dictates American electoral behavior. Yet Americans often participate in elections in which either the partisanship of candidates is unknown or candidates from the same party compete, rendering the partisan cue meaningless. In this research, we examine how candidate demographics—specifically gender—relate to voter behavior and candidate selection in these contexts. Leveraging survey data from same-party matchups in congressional elections (resulting from "top-two primaries"), we examine the relationship between candidate gender and undervoting and vote choice. We find that in same-party matchups, women candidates are associated with lower levels of undervoting among women voters. Furthermore, we find that in mixed-gender contests, women voters from both parties and Democratic men are more likely to favor female candidates. The findings presented here have important implications for the literatures on gender and politics, electoral politics, partisanship, and the design of electoral institutions.